Perilaku Gelandangan Dalam Pemanfaatan Pelayanan Kesehatan Masyarakat Di Kota Semarang Jawa Tengah (Studi Kasus di Kawasan Pasar Johar) - Cahyo, Kusyogo; Hidayatullah, M. Syarif; Widjanarko, Bagoes (Jurnal Promosi Kesehatan Indonesia, 2006)
Background : Vagrants are an interesting and critical social phenomenon where their numbers in large cities is steadily increasing. They have been generally vulnerable from many health problems and hence they have a high risk of various diseases. Poverty, illiteracy, lack of assets and production means, unemployment and many other factors have made them never using health facilities and services. This research is therefore, intended to discribe health seeking behaviour of the vagrants who usually stay in the area of Johar market Semarang.Method : This study applies a qualitative approach. In-depth interviews have been used to collect the data from 18 selected respondents. Snowball sampling technique has been employed to find respondents.Results : The study found that most vagrants have lack of knowledge primarily in terms of disease preventions, health protections and promotion. Their perceptions about sickness is acondition when they feel unable to do their daily activities anymore. Generally, they seldomknow the type of diseases they are suffering from, but they only feel the pain. The kind of preventive and curative measures which they adopt often based on information obtained from their friends. When they feel pain or sick, they just treat themselves by taking some medicines which bought in drug store or taking some traditional herbs (Jamu). The majority of va-grants have never visited health center because they could not afford to pay, feel embarassed, fear to be refused by health personnels. Importantly, they feel that they have never obtained a serious illness.Keywords : Vagrant, health seeking behaviour, qualitative method.